Temporal assessment of the medicinal plants trade in public markets of the state of Paraíba, northeastern Brazil - Ezequiel da Costa Ferreira; Reinado Farias Paiva de Lucena; Rainer W. Bussmann; Narel Y. Paniagua-Zambrana; Denise Dias da Cruz (BMC, 2021)
Abstract Background Open and public markets are the main providers of medicinal plants in urban environments. The present study evaluated the medicinal plants sold in public markets in different municipalities in the mesoregions of the state of Paraíba, northeast of Brazil, and the possible variations in the supply of these plants in the markets over the course of a year. Methods Interviews with medicinal plant traders were conducted in four mesoregions of different climatic and phytophysiognomic characteristics (ranging from Caatinga to Atlantic Forest). The versatility of the species sold was elucidated using the relative importance (RI) index, and the set of species sold by each informant in each mesoregion was compared with each other by one-way Anosim  and by the analysis of main coordinates. Results Thirty-five plant traders identified 163 medicinal plant species (151 genders and 76 families) and more 17 non identified species. The most frequent families were Fabaceae (19 species), Asteraceae (12), Lamiaceae (11), and Myrtaceae (6). Punica granatum, Zingiber officinale, and Myracrodruon urundeuva were the species with the highest RI. The analysis of similarity showed distinct differences between the Sertão and all other mesoregions. The Agreste, an ecotone area, was also the area where more species of other regions was found. The absence of 88 species in at least one of the trading locations at some stage of the fieldwork was recorded. Conclusions The presence and absence of the commercialized species do not seem to be related to the period of the year or the mesoregion. There were differences in the inventory of plants commercialized in markets in recent years. We identified an intermediate zone of knowledge and use of species commercialized between the studied localities.